The cardiac arrest centre for the treatment of sudden cardiac arrest due to presumed cardiac cause – aims, function and structure: Position paper of the Association for Acute CardioVascular Care of the European Society of Cardiology (AVCV), European Association of Percutaneous Coronary Interventions (EAPCI), European Heart Rhythm Association (EHRA), European Resuscitation Council (ERC), European Society for Emergency Medicine (EUSEM) and European Society of Intensive Care Medicine (ESICM). Issue 4 (November 2020) - Sinning, Christoph; Ahrens, Ingo; Cariou, Alain; Beygui, Farzin; Lamhaut, Lionel; Halvorsen, Sigrun; Nikolaou, Nikolaos; Nolan, Jerry P; Price, Susanna; Monsieurs, Koenraad; Behringer, Wilhelm; Cecconi, Maurizio; et al.
Approximately 10% of patients resuscitated from out-of-hospital cardiac arrest survive to hospital discharge. Improved management to improve outcomes is required, and it is proposed that such patients should be preferentially treated in cardiac arrest centres. The minimum requirements of therapy modalities for the cardiac arrest centre are 24/7 availability of an on-site coronary angiography laboratory, an emergency department, an intensive care unit, imaging facilities such as echocardiography, computed tomography and magnetic resonance imaging, and a protocol outlining transfer of selected patients to cardiac arrest centres with additional resources (out-of-hospital cardiac arrest hub hospitals). These hub hospitals are regularly treating a high volume of patients and offer further treatment modalities. This consensus document describes the aims, the minimal requirements for therapeutic modalities and expertise, and the structure, of a cardiac arrest centre. It represents a consensus among the major European medical associations and societies involved in the treatment of out-of-hospital cardiac arrest patients.